Transition Metal Complex of Oxadiazole as Dual Antidiabetic and Anti Hyperthyroid Agent - Alnawas, Zahraa Ali Nashoor (Indonesian Journal on Health Science and Medicine, 2025)
General background: 1,3,4-oxadiazole derivatives are well-established heterocycles with broad pharmacological potential, and metal coordination frequently enhances their therapeutic profiles. Specific background: Recent studies highlight the need for compounds capable of dual modulation of metabolic and endocrine disorders, particularly diabetes and hyperthyroidism, where single-target therapies often yield limited outcomes. Knowledge gap: Despite promising reports, few studies have integrated experimental pharmacology with quantum chemical modeling to explain how metal coordination influences biological potency. Aims: This research synthesized a new oxadiazole–indolinone ligand and its Co(II), Ni(II), Cr(III), and Fe(III) complexes and evaluated their antidiabetic and anti-hyperthyroid activities through in vivo assays supported by DFT calculations and molecular docking. Results: All complexes demonstrated dose-dependent activity, with Co(II) exhibiting the strongest glucose reduction (120 ± 7 mg/dL) and T₄ suppression (7.1 ± 0.4 µg/dL), consistent with superior docking affinities and favorable electronic descriptors. Novelty: This study correlates spectroscopic, computational, docking, and pharmacological findings in a unified structure–activity interpretation. Implications: The results indicate that metal coordination significantly boosts biological efficacy, positioning Co(II) complexes as strong candidates for future dual-action therapeutics in diabetes and hyperthyroidism.Highlight : Metal complexation improves biological effectiveness of the ligand. Co(II) complex shows the strongest dual activity based on results. Docking findings align with experimental data, supporting the SAR. Keywords : 1,3,4-Oxadiazole, Transition Metal Complexes, DFT, Molecular Docking, Antidiabetic and Anti-Hyperthyroid Activity